Designing a secure fail-safe cloud repository of paperworks of students and employees of educational institutions - Kochyn, Viktor P.; Zherelo, Anatolii V. (Journal of the Belarusian State University. Mathematics and Informatics, 2021)
The article discusses the main approaches to the design and development of an automated information system for a secure cloud repository of paperworks of students and employees of educational and research organisations (abstracts, essays, term papers and theses, master’s theses, deposited articles), providing secure storage and secure mobile access to stored data. The research and development of architectural solutions to ensure reliable and secure data storage using cloud technologies are described. The main problems of designing a secure repository and ways to solve them are considered. The cloud repository of written works is built on the basis of the Ceph distributed file system, which uses the NextCloud system and the virtual computing resources of the virtual network infrastructure of the Belarusian State University as a platform for building a cloud interface.
Keywords: cloud computing; information systems design; educational technologies; secure cloud storage; virtualisation; network infrastructure